Method for producing mixed-phase excited gypsum under liquid-phase mixed acid system formed by phosphoric acid and sulfuric acid as well as product and application thereof
By treating dihydrate gypsum in a liquid-phase mixed acid system of phosphoric acid and sulfuric acid, solid-liquid separation is used for solid-liquid separation, low-phosphorus and low-fluorine-containing mixed-phase gypsum, solving the storage and processing costs of industrial by-product gypsum High problems achieve efficient gypsum treatment and the application of a variety of building materials.
Patent Information
- Application Number
- CN202411531470.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
AI Technical Summary
The existing technology failed to effectively utilize dihydrate gypsum, resulting in the storage of industrial by-product gypsum, and the mixed phase stimulated the processing technology of gypsum with high cost and unstable ratio of two-phase materials, and lacks the preparation of mixing under the phosphoric acid sulfuric acid liquid-phase mixed acid system. Methods for phase-exciting gypsum.
Under the liquid-phase mixed acid system formed by phosphoric acid and sulfuric acid, dihydrate gypsum is added to the mixed acid material containing sulfuric acid, phosphoric acid and crystallization agent in a solid-liquid ratio of 1:2-6, and the temperature is raised and solid-liquid separation is carried out to obtain A mixed phase excitation gypsum with low phosphorus and low fluorine content, and the crystallization agent is a combination of iron oxide, aluminum oxide, magnesium oxide and fluorosiliic acid.
It has achieved harmless treatment. The harmful components of the product have extremely low content of phosphorus and fluorine, and have good processing performance. It is suitable for building materials and cement production, reducing process filtration and conveying scaling problems, and can be used in the production of a variety of building materials.
Smart Images

Figure CN119263665A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gypsum processing, in particular to a method for producing mixed-phase activated gypsum in a liquid-phase mixed acid system formed by phosphoric acid and sulfuric acid, and a product and application thereof. Background Art
[0002] Dihydrate gypsum: also known as gypsum or raw gypsum, is a stable gypsum phase in nature. The main component of most industrial by-product gypsum is dihydrate gypsum. Industrial by-product gypsum includes flue gas desulfurization gypsum, phosphogypsum, titanium gypsum, salt gypsum, citric acid gypsum, boric gypsum, etc. At present, the output of industrial by-product dihydrate gypsum is more than 200 million tons / year, but only 120 million tons / year can be consumed, and more than 80 million tons / year are stored. Industrial by-product gypsum has a large content of soluble impurities, high requirements for harmless treatment, high investment and operating costs, and has a certain negative impact on its comprehensive utilization. my country is the country with the largest production and storage of industrial by-product gypsum in the world.
[0003] Hemihydrate gypsum is a kind of dihydrate gypsum (CaSO 4 ·2H 2 O) is a product obtained by heating and dehydration, the main component of which is calcium sulfate hemihydrate (CaSO 4 1 / 2H 2 O). According to the different formation conditions, hemihydrate gypsum can be divided into two variants: α-hemihydrate gypsum and β-hemihydrate gypsum.
[0004] There are two types of anhydrous type II gypsum: natural and artificial. Due to its good stability, it can be used as a high-quality substitute for heavy calcium carbonate, talcum powder, etc. as a filler, and can also be used as a raw material for high-quality building materials.
[0005] The harmless treatment of dihydrate phosphogypsum refers to the measures taken to reduce harmful substances such as phosphorus, fluorine, organic matter, free acid, etc. in it by means of water washing, flotation, lime neutralization, high-temperature calcination, etc. to meet the requirements of comprehensive utilization of phosphogypsum. At present, there are related studies that use dihydrate gypsum as raw material to prepare it into semi-hydrated or anhydrous gypsum while removing phosphorus and fluorine elements.
[0006] For example, patent CN105174760B is a method for preparing α-hemihydrate gypsum from dihydrate gypsum, wherein dihydrate gypsum and a crystallization agent are added to a mixed acid aqueous solution containing sulfuric acid and phosphoric acid for crystallization reaction, solid-liquid separation, part of the liquid phase is returned to the crystallization tank for further crystallization reaction, and the other part is transported to the acid decomposition tank for preparing phosphoric acid by sulfuric acid decomposition of phosphate ore for utilization; the solid phase is washed with washing water, and the washing water is introduced into the liquid phase obtained above for utilization. The solid phase obtained by washing can be dried into α-hemihydrate gypsum powder, or directly added with water without drying to make gypsum products such as gypsum board, gypsum block, gypsum component, etc.
[0007] Another example is patent CN113772709B, which is a method for preparing anhydrous micron calcium sulfate using phosphogypsum, wherein water, acid, nucleating agent and crystal control agent are added to phosphogypsum and heated for reaction, and then filtered and dried to obtain micron-grade anhydrous calcium sulfate. The core is mainly sulfuric acid, and the acid can be sulfuric acid, or a mixture of sulfuric acid and any one of phosphoric acid, hydrochloric acid and nitric acid.
[0008] Therefore, the harmless treatment of dihydrate gypsum to reduce the phosphorus and fluorine content and improve the properties and applications of the final product is still the current key research object, and further research is needed to obtain technical solutions with better economic benefits, product properties and application.
[0009] At present, mixed-phase activated gypsum mainly refers to a product formed by mixing gypsum of different phases (such as hemihydrate gypsum and type II anhydrous gypsum) in a certain proportion. Hemihydrate gypsum can be either β gypsum or α gypsum. Advantages of mixed-phase activated gypsum: adjustable setting time, high strength, good crack resistance, good construction performance, environmental protection and energy saving. At present, most mixed-phase activated gypsum on the market is a mixture of β gypsum and anhydrous type II gypsum. Existing processing technologies for mixed-phase activated gypsum: canning method and mixing method. The canning method refers to the process of drying dihydrate gypsum at 100+℃ to a semi-hydrated state (β), and then using the waste heat to put it in a special sealing device to convert part of the hemihydrate gypsum into anhydrous type II gypsum. The advantage of the canning method is that it can be processed into mixed-phase activated gypsum in one go, and the disadvantage is that the ratio of the two-phase materials is unstable, which causes great difficulties on the application end. The mixing method is a method of mixing hemihydrate gypsum and anhydrous type II gypsum in a certain proportion. The advantage is that the product composition is stable and the performance is stable, and the disadvantage is that the cost of the mixed product is high.
[0010] At present, there is no disclosure on the preparation of mixed-phase activated gypsum by using dihydrate gypsum in a phosphoric acid and sulfuric acid liquid phase mixed acid system. Summary of the invention
[0011] In order to solve the above technical problems existing in the prior art, the present invention provides a method for producing mixed-phase activated gypsum in a liquid-phase mixed acid system formed by phosphoric acid and sulfuric acid.
[0012] A method for producing mixed-phase activated gypsum in a liquid-phase mixed acid system formed by phosphoric acid and sulfuric acid, specifically comprising the following steps:
[0013] (1) adding dihydrate gypsum to a mixed acid slurry containing sulfuric acid, phosphoric acid, and a crystal-changing agent at a solid-liquid ratio of 1:(2-6) to prepare a mixed slurry A;
[0014] (2) heating the mixed slurry A to 80-105° C. and reacting for 2-8 hours to obtain a mixed phase activated gypsum slurry B;
[0015] (3) The mixed slurry B is subjected to solid-liquid separation to obtain a solid phase C and a filtrate D. The solid phase C is washed with clean water to obtain a solid phase E and a washing liquid F. The solid phase E is the mixed phase activated gypsum.
[0016] Furthermore, the mixed slurry contains 2 O 5 % accounts for 3-16% of the total mass of the liquid phase in the mixed acid slurry A.
[0017] Furthermore, the crystal-changing agent is a combination of 3-4 inorganic salt oxides, preferably a combination of iron oxide, aluminum oxide, magnesium oxide, and fluorosilicic acid.
[0018] Furthermore, the amount of the crystal-changing agent added accounts for 2-12% of the total mass of the mixed slurry A.
[0019] Furthermore, the iron oxide content is 0.2-3.0%, aluminum oxide is 0.2-2.0%, magnesium oxide is 0.5-7.0%, and fluorosilicic acid is 0.5-4.0%.
[0020] Furthermore, the dihydrate gypsum raw material is mainly industrial by-product gypsum (such as flue gas desulfurization gypsum, phosphogypsum, titanium gypsum, salt gypsum, citric acid gypsum, boric gypsum, etc.).
[0021] Furthermore, the filtrate D and washing liquid F are recovered and used for phosphate rock extraction.
[0022] The above method is used to reduce the harmful components of phosphorus and fluorine in gypsum. This method can be used to treat most industrial by-product dihydrate gypsum, such as phosphogypsum, desulfurized gypsum, citric acid gypsum, etc., especially in the wet phosphoric acid industry, where it has more obvious advantages. The final product, i.e., mixed-phase gypsum, can meet the standard of harmless treatment. The harmful components of phosphorus and fluorine in the mixed-phase activated gypsum by-product obtained by the system treatment are very low: the total phosphorus of the product is less than 0.2%, the water-soluble phosphorus is less than 0.1%, and the water-soluble fluorine is less than 0.1%, which can meet the needs of most industries now.
[0023] The mixed phase activated gypsum prepared by the above method can be widely used in the preparation of building materials, gypsum acid-making and cement co-production, mine filling, etc. The final mixed phase activated gypsum has good processing performance. In the liquid phase wet-based state, the performance can remain stable for a long time, and it will not hydrate and agglomerate for 16-40 hours, which can reduce the scaling and agglomeration problems of the process filtration and transportation system; and after adding the activator, a highly active building material product can be obtained. The wet-based product can be directly used in the processing of building materials, gypsum acid-making and cement co-production, mine filling, etc., and can also be dried into powder and activated to process gypsum blocks, gypsum strips, gypsum-based self-leveling mortar and other products.
[0024] Compared with the prior art, the technical effects created by the present invention are embodied in:
[0025] 1. The present invention adds traditional dihydrate gypsum to a new phosphoric acid + sulfuric acid liquid phase mixed acid system, controls the temperature and reaction time, and obtains a product different from traditional gypsum - mixed phase activated gypsum. The technology specifically adds dihydrate gypsum to a mixed solution containing phosphoric acid and sulfuric acid, then adds a crystallization agent, heats the temperature to 80-105°C, reacts for 2-8 hours, and separates the solid and liquid and washes with clean water to obtain mixed phase activated gypsum containing about 20% water. The above-mentioned gypsum wet-based product can be directly used in the processing of building materials, gypsum acid production and cement co-production, mine filling, etc.; mixed phase activated gypsum powder can be obtained by drying, and the mixed phase activated gypsum powder can be used as a raw material for building materials. The solid-liquid separation filtrate can continue to react with phosphate rock to extract and prepare phosphoric acid.
[0026] 2. The reaction conditions of the present invention are as follows: dihydrate gypsum is added to a liquid mixed acid slurry containing sulfuric acid, phosphoric acid and a crystal-changing agent at a solid-liquid ratio of 1:2-6 to prepare a mixed slurry A; P 2 O 5 % accounts for 3-16% of the total mass of the liquid phase in the mixed acid slurry A. The mixed slurry is heated to 80-105°C and reacted for 2-8 hours to obtain a mixed phase excited gypsum slurry B. The amount of the crystallization agent added accounts for 2-12% of the total mass of the material A. The crystallization agent is a combination of 3-4 inorganic salt oxides. The mixed slurry B is subjected to solid-liquid separation to obtain a solid phase C and a filtrate D. The solid phase C is washed with clean water to obtain a solid phase E and a washing liquid F. The filtrate D and the washing liquid F are recovered and used for phosphate rock extraction.
[0027] 3. The present invention innovates the acidic system: the acidic system is composed of sulfuric acid, phosphoric acid and a crystal-changing agent, wherein P 2 O 5 % accounts for 3-16% of the total mass of the liquid phase in the mixed acid slurry A. In this acidic system range, adjust P 2 O 5 %, crystal-changing agent content and temperature can obtain mixed-phase activated gypsum with different gypsum three-phase compositions, different particle sizes and different crystal shapes in the present application.
[0028] 4. The invention innovates the crystal-transforming agent composition: the crystal-transforming agent is composed of four combinations of iron oxide, aluminum oxide, magnesium oxide and fluosilicic acid, and its total mass accounts for 2-12% of the material components, among which the content of iron oxide is 0.2-3.0%, aluminum oxide is 0.2-2.0%, magnesium oxide is 0.5-7.0%, and fluosilicic acid is 0.5-4.0%. Adjusting the amount of the crystal-transforming agent in the slurry can adjust the crystal-transforming time and the solidification time of the mixed phase gypsum.
[0029] 5. The present invention uses a specific acidic system and a crystal-changing agent to obtain a mixed phase activated gypsum composition: anhydrous phase accounts for 40%-60%, semi-aqueous phase accounts for 15-30%, and dihydrate phase accounts for 3-20%. The content of impurities (harmful components phosphorus and fluorine) in the product is very low: the total phosphorus in the obtained product is less than 0.2%, the water-soluble phosphorus is less than 0.1%, and the water-soluble fluorine is less than 0.1%. This product can meet the needs of most industries now.
[0030] 6. The mixed phase activated gypsum obtained by the present invention has good processing performance. In the liquid phase wet-based state, the performance can remain stable for a long time, and it will not hydrate and agglomerate for 16-40 hours, which can reduce the scaling and agglomeration problems of the process filtration and transportation system; after adding the activator, a highly active building material product can be obtained, and the wet-based product can be directly used to process building materials, such as gypsum blocks, gypsum strips, paper-faced / non-paper-faced gypsum boards and other projects, which can obtain very low use costs; the wet-based product can be used as a raw material for gypsum acid co-production of cement after hydration; the wet-based product can be directly used as a raw material for mine filling; the wet-based product can also be dried into powder and then activated to process gypsum blocks, gypsum strips, gypsum-based self-leveling mortar and other products, which can replace building gypsum in many building materials fields.
[0031] 7. The raw material of dihydrate gypsum used in the present invention is mainly industrial by-product gypsum such as flue gas desulfurization gypsum, phosphogypsum, titanium gypsum, salt gypsum, citric acid gypsum, boric gypsum, etc., which develops a new idea for the treatment of industrial by-product dihydrate gypsum; solves the world's difficult problem of industrial by-product gypsum solid waste treatment, and converts dihydrate gypsum into a useful gypsum cementitious material - mixed phase activated gypsum in a liquid acid system. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further defined below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.
[0034] Example 1
[0035] (1) Dihydrate gypsum (phosphogypsum) is added to a mixed acid slurry containing sulfuric acid, phosphoric acid, and a crystal-changing agent at a solid-liquid ratio of 1:3 to prepare a mixed acid slurry A; the liquid phase P in the mixed acid slurry A is 2 O 5 % content 7%, crystal conversion agent content 5.8%. The specific content of crystal conversion agent is: iron oxide content 0.7%, aluminum oxide 0.8%, magnesium oxide 2.0%, fluorosilicic acid 2.3%.
[0036] (2) The mixed slurry A is heated to 90° C. and reacted for 5 hours to obtain a mixed phase activated gypsum slurry B.
[0037] (3) The mixed slurry B is subjected to solid-liquid separation to obtain a solid phase C and a filtrate D. The solid phase is washed with clean water to obtain a mixed phase activated gypsum E.
[0038] The composition of the mixed phase activated gypsum obtained in Example 1 was tested, and the details are as follows:
[0039] According to GB / T 5484-2012 phosphomolybdenum blue spectrophotometry, the phosphorus in the product is tested, including total phosphorus: 0.15%, water-soluble phosphorus: 0.06%; according to GB / T 5484-2012 fluoride ion selective electrode method for determination of water-soluble fluorine: 0.08%; the "GB / T36141-2018" oven method was used to detect the three phases of gypsum. The composition of fresh gypsum just produced was 45.8% anhydrous phase, 29.7% semi-aqueous phase, 14.3% dihydrate phase, and 10.0% acid insoluble matter; wet-based fresh gypsum stability data: after natural placement for 18 hours, the three phases of gypsum were: 45.5% anhydrous phase, 28.3% semi-aqueous phase, 15.3% dihydrate phase, and 10.1% acid insoluble matter; mixed-phase gypsum excitation activity: 2 hours after the activator was added to the fresh gypsum, the three phases of gypsum changed to: 10.5% anhydrous phase, 1.3% semi-aqueous phase, 78.7% dihydrate phase, and 9.8% acid insoluble matter.
[0040] Example 2
[0041] (1) Dihydrate gypsum (phosphogypsum) is added to a mixed acid slurry containing sulfuric acid, phosphoric acid, and a crystal-changing agent at a solid-liquid ratio of 1:4 to prepare a mixed acid slurry A; 2 O 5 % content 15%, crystal conversion agent content 6.6%. The specific content of crystal conversion agent is: iron oxide content 1.5%, aluminum oxide 0.6%, magnesium oxide 1.5%, fluorosilicic acid 3.0%.
[0042] (2) The mixed slurry A was heated to 93° C. and reacted for 4 hours to obtain a mixed phase activated gypsum slurry B.
[0043] (3) The mixed slurry B is subjected to solid-liquid separation to obtain a solid phase C and a filtrate D. The solid phase is washed with clean water to obtain a mixed phase activated gypsum E.
[0044] The composition of the mixed phase activated gypsum obtained in Example 2 was simply tested: the phosphorus in the product was tested according to the phosphomolybdenum blue spectrophotometry method in accordance with GB / T5484-2012, where the total phosphorus was 0.18% and the water-soluble phosphorus was 0.06%; 5484-2012 fluoride ion selective electrode method for determination of water-soluble fluorine: 0.05%; the "GB / T36141-2018" oven method was used to detect the three phases of gypsum. The composition of fresh gypsum just produced was 57.8% anhydrous phase, 20.1% semi-aqueous phase, 15.9% dihydrate phase, and 9.5% acid insoluble matter; wet-based fresh gypsum stability data: after natural placement for 18 hours, the three phases of gypsum were: 54.5% anhydrous phase, 23.3% semi-aqueous phase, 17.1% dihydrate phase, and 9.1% acid insoluble matter; mixed-phase gypsum excitation activity: 2 hours after the activator was added to the fresh gypsum, the three phases of gypsum changed to: 16.5% anhydrous phase, 2.3% semi-aqueous phase, 73.7% dihydrate phase, and 9.8% acid insoluble matter.
[0045] Example 3
[0046] (1) Dihydrate gypsum (desulfurized gypsum) is added to a mixed acid slurry containing sulfuric acid, phosphoric acid, and a crystal-changing agent at a solid-liquid ratio of 1:4 to prepare a mixed slurry A; 2 O 5 % content 15%, crystal conversion agent content 5.5%. The specific content of crystal conversion agent is: iron oxide content 0.5%, aluminum oxide 1.0%, magnesium oxide 2.1%, fluorosilicic acid 1.9%.
[0047] (2) The mixed slurry A is heated to 88° C. and reacted for 5 hours to obtain a mixed phase activated gypsum slurry B.
[0048] (3) The mixed slurry B is subjected to solid-liquid separation to obtain a solid phase C and a filtrate D. The solid phase is washed with clean water to obtain a mixed phase activated gypsum E.
[0049] The composition of the mixed phase activated gypsum obtained in Example 3 was simply tested: the phosphorus in the product was detected according to the GB / T5484-2012 phosphomolybdenum blue spectrophotometry method, where the total phosphorus was 0.09% and the water-soluble phosphorus was 0.04%; according to GB / T 5484-2012 fluoride ion selective electrode method for determination of water-soluble fluorine: 0.05%; the "GB / T36141-2018" oven method was used to detect the three phases of gypsum. The composition of fresh gypsum just produced was 57.9% anhydrous phase, 18.1% semi-aqueous phase, 19.6% dihydrate phase, and 3.5% acid insoluble matter; wet-based fresh gypsum stability data: after natural placement for 18 hours, the three phases of gypsum were: 53.5% anhydrous phase, 21.3% semi-aqueous phase, 21.7% dihydrate phase, and 3.1% acid insoluble matter; mixed-phase gypsum excitation activity: 2 hours after the activator was added to the fresh gypsum, the three phases of gypsum changed to: 8.5% anhydrous phase, 13.3% semi-aqueous phase, 74.7% dihydrate phase, and 3.9% acid insoluble matter.
[0050] Example 4
[0051] (1) Dihydrate gypsum (citric acid gypsum) is added to a mixed acid slurry containing sulfuric acid, phosphoric acid, and a crystal-changing agent at a solid-liquid ratio of 1:4 to prepare a mixed acid slurry A; 2 O 5 % content 15%, crystal conversion agent content 9.0%. The specific content of crystal conversion agent is: iron oxide content 0.9%, aluminum oxide 0.4%, magnesium oxide 5.0%, fluorosilicic acid 2.7%.
[0052] (2) The mixed slurry A is heated to 88° C. and reacted for 5 hours to obtain a mixed phase activated gypsum slurry B.
[0053] (3) The mixed slurry B is subjected to solid-liquid separation to obtain a solid phase C and a filtrate D. The solid phase is washed with clean water to obtain a mixed phase activated gypsum E.
[0054] The composition of the mixed phase activated gypsum obtained in Example 4 was simply tested: the phosphorus in the product was tested according to the phosphomolybdenum blue spectrophotometry method in accordance with GB / T5484-2012, where the total phosphorus was 0.14% and the water-soluble phosphorus was 0.07%; 5484-2012 fluoride ion selective electrode method for determination of water-soluble fluorine: 0.04%; the "GB / T36141-2018" oven method was used to detect the three phases of gypsum. The composition of fresh gypsum just produced was 53.9% anhydrous phase, 28.1% semi-aqueous phase, 17.6% dihydrate phase, and 0.5% acid insoluble matter; wet-based fresh gypsum stability data: after natural placement for 18 hours, the three phases of gypsum were: 52.5% anhydrous phase, 30.3% semi-aqueous phase, 18.1% dihydrate phase, and 0.3% acid insoluble matter; mixed-phase gypsum excitation activity: 2 hours after the activator was added to the fresh gypsum, the three phases of gypsum changed to: 17.1% anhydrous phase, 14.3% semi-aqueous phase, 68.7% dihydrate phase, and 0.9% acid insoluble matter.
[0055] Finally, it should be pointed out that the above embodiments are only representative examples of the present invention. Obviously, the technical solution of the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by ordinary technicians in this field should be considered as the protection scope of the present invention.
Claims
1. A method for producing mixed-phase activated gypsum in a liquid-phase mixed acid system formed by phosphoric acid and sulfuric acid, characterized in that: The specific steps include: (1) adding dihydrate gypsum to a mixed acid slurry containing sulfuric acid, phosphoric acid, and a crystal-changing agent at a solid-liquid ratio of 1:(2-6) to prepare a mixed slurry A; (2) heating the mixed slurry A to 80-105° C. and reacting for 2-8 hours to obtain a mixed phase activated gypsum slurry B; (3) The mixed slurry B is subjected to solid-liquid separation to obtain a solid phase C and a filtrate D. The solid phase C is washed with clean water to obtain a solid phase E and a washing liquid F. The solid phase E is the mixed phase activated gypsum.
2. The method according to claim 1, characterized in that: The P2O5% in the mixed slurry A accounts for 3-16% of the total mass of the liquid phase in the mixed slurry A.
3. The method according to claim 1, characterized in that The crystal-changing agent is a combination of 3-4 inorganic salt oxides.
4. The method according to claim 3, characterized in that The crystal-changing agent is a combination of iron oxide, aluminum oxide, magnesium oxide and fluorosilicic acid.
5. The method according to claim 4, characterized in that The amount of the crystal-changing agent added is 2-12% of the total mass of the mixed slurry A.
6. The method according to claim 5, characterized in that The iron oxide content is 0.2-3.0%, the aluminum oxide content is 0.2-2.0%, the magnesium oxide content is 0.5-7.0%, and the fluorosilicic acid content is 0.5-4.0%.
7. The method according to claim 1, characterized in that The dihydrate gypsum raw material is industrial by-product gypsum.
8. Use of the method according to any one of claims 1 to 7 in reducing harmful components such as phosphorus and fluorine in gypsum.
9. Mixed-phase activated gypsum prepared by the method according to any one of claims 1 to 7.
10. Application of the mixed phase activated gypsum according to claim 9 in building material raw materials, gypsum acid production and cement co-production raw materials, mine filling raw materials, etc.
Citation Information
Patent Citations
A method for preparing α - hemihydrate gypsum from dihydrate gypsum
CN105174760B